Potential of Kaolin Clay on Formulation of Water Based Drilling Mud Reinforced with Biopolymer, Surfactant, and Limestone - Omary, Paul M.; Ricky, Emanuel X.; Kasimu, Naswibu A.; Madirisha, Makungu M.; Kilulya, Kessy F.; Lugwisha, Esther H. J. (Tanzania Journal of Science, 2023)
Drilling the wellbore into subsurface formations is the earliest stage in the life of a well that requires a suitable drilling fluid with good rheological and filtration control characteristics to achieve a successful drilling operation. This paper reports on the formulation of water-based drilling mud using kaolin clay reinforced with biopolymer, surfactant, and limestone from Tanzania. The raw materials used for the formulation were characterized using XRD, XRF, FTIR, and TGA techniques. The rheological properties, filtration loss, pH, and density of the formulated mud were measured using a viscometer, filter press, pH meter, and mud balance, respectively. The XRD results revealed kaolinite and quartz as the main minerals in all kaolin clay samples which were in agreement with the FTIR findings. The mineralogical composition of the kaolin was observed to vary with the mining sites and influenced the rheological and filtration control characteristics of the mud. The beneficiated drilling mud showed better rheological and filtration control characteristics than the commercially available bentonite mud in Dar es Salaam market and was comparable with the API standards. These results, therefore, are not only new but rather important and novel information on the potential of kaolin clay for the formulation of water based drilling mud. Keywords: Water-based drilling mud, kaolin clay, biopolymers, bentonite, surfactant